2008
DOI: 10.1115/1.2978993
|View full text |Cite
|
Sign up to set email alerts
|

Computational Dynamics of a Thermally Decomposable Viscoelastic Lubricant Under Shear

Abstract: The effect of viscoelasticity on the thermodynamic performance of a thermally decomposable lubricant subjected to shear and Arrhenius kinetics is investigated with direct numerical simulations. A numerical algorithm based on the finite difference method is implemented in time and space with the Oldroyd-B constitutive equation as the model for the viscoelastic liquids. We report enhanced efficiency in the case of a polymeric lubricant as compared with the purely viscous lubricant. In particular, it is demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 13 publications
2
57
0
Order By: Relevance
“…For ξ = 1, these are first-order accurate in time but second order in space. The schemes in Chinyoka [19] have ξ = 1/2, which improves the accuracy in time to second order. As in Chinyoka [8,9,20] we, however, use ξ = 1 here so that we are free to choose larger time steps and still converge to the steady solutions.…”
Section: Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ξ = 1, these are first-order accurate in time but second order in space. The schemes in Chinyoka [19] have ξ = 1/2, which improves the accuracy in time to second order. As in Chinyoka [8,9,20] we, however, use ξ = 1 here so that we are free to choose larger time steps and still converge to the steady solutions.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…Our numerical algorithm is based on the semi-implicit finite difference scheme [8,9,[17][18][19][20]. Implicit terms are taken at the intermediate time level…”
Section: Numerical Solutionmentioning
confidence: 99%
“…In either case the fluid viscosity will be considered temperature dependent and our investigations will focus on the fluids' heat transfer characteristics in simple flows. As in Chinyoka (2008;2009a;b;2010;2011) the viscoelastic fluid behavior is compared to that for corresponding inelastic (Newtonian and/or Generalized Newtonian) fluids and it is demonstrated that depending on the physical application, viscoelasticity may or may not be favorable. For a comprehensive overview of non-Newtonian flows in general and viscoelastic fluid phenomena in particular, we refer to the excellent treatises of Bird et al (1987);Ferry (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Our current investigations with Johnson-Segalman fluids show that the answer is negative. The viscoelastic models used in Chinyoka (2008;2009a;b;2010;2011) exhibit a monotonic shear stress/shear rate relationship in simple shear flows. The Johnson-Segalman fluid, allows for a non-monotonic relationship between the shear stress and rate of shear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation